Differences in performance indicator between winning and losing team in formative stages according to sex and final score differences - Antonio Antúnez Medina; Javier García Rubio; Francisco Javier Sáez Blázquez; Andrea Valle Blanco; Álvaro García Martín (Federación Extremeña de Balonmano; University of Extremadura, 2013)
The aim of this study was to analyze an u´14 handball competition in function of gender and final score differences, trying to identify performance indicators that differentiate winning teams from losing team in the 2011 Spanish Championship. An amount of 47 masculine and 45 feminine matches from the 2011 Spanish u´14 Championship were analyzed. The analysis was developed with specific software SPSS 17.0 for Windows. A cluster analysis was carried out in function of the final score differences, as well as a t test for independent samples or a Mann- Whitney U in relation of normality, random and  homoscedasticity tests. Results show that, in both competitions, winning teams reach more goals from 6 m line, fewer errors in pass-reception, as well as better values of Offensive Efficacy Coefficient (OEC) and Offensive Realization Coefficcient (ORC) versus looser teams. Failed and stopped shoots from free throw line differentiate winner teams is male competitions. The amount of possession, penalty goals and steps differentiate winner teams from looser ones in female competitions. Results highlight how important are the physical condition and the individual technic for this ages. Key words: Win-lose, U14, Sport performance